Modeling the implementation of green initiatives: An AHP-BOCR approach. Issue 1 (1st January 2018) - Sarmiento, Roberto; Vargas-Berrones, Karla Ximena
Abstract: Over the past few decades, there has been a growing need for businesses to become more environmentally friendly in their operations, products and services. However, the decision to undertake initiatives or programs that can help them achieve this goal is complex. While there are clear and desirable ecological benefits from these efforts, it is possible that there are also negative aspects that have to be considered. Our investigation presents a theoretical model that captures the variables, processes and dynamics involved in the decision to implement/not implement a green initiative. More specifically, we propose an analytic hierarchy process model that takes into account the benefits, opportunities, costs and risks that are associated with the potential implementation of these types of programs. A simulated example shows the utility of our proposed framework. Opportunities for future research are laid out.